2019
DOI: 10.1155/2019/1856294
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and an Antineuroinflammatory Lignan, Savinin from the Roots of Acanthopanax henryi

Abstract: The phytochemical investigation on the roots of Acanthopanax henryi (Araliaceae) resulted in the discovery of twenty compounds whose chemical structures were elucidated by the analysis of 1D-, 2D-NMR, mass spectrometry data, other physicochemical properties, and a comparison of the spectral data with the literature. They were identified as (-)-sesamin (1), helioxanthin (2), savinin (3), taiwanin C (4), 6-methoxy-7-hydroxycoumarin (5), behenic acid (6), 3-O-caffeoyl-quinic acid (7), 5-O-caffeoyl-quinic acid (8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…CA is a nontoxic compound extracted from natural plants. It is proved that CA can protect cells from radiation and neuroinflammation [ 58 , 59 ]. Akram et al [ 26 ] found the inhibitory effect of CA on paw edema of rat models induced by carrageenan (CRG).…”
Section: Discussionmentioning
confidence: 99%
“…CA is a nontoxic compound extracted from natural plants. It is proved that CA can protect cells from radiation and neuroinflammation [ 58 , 59 ]. Akram et al [ 26 ] found the inhibitory effect of CA on paw edema of rat models induced by carrageenan (CRG).…”
Section: Discussionmentioning
confidence: 99%
“…The top 6 ingredients were kaempferol (SCP93), apigenin (DS77), 7-methoxy-2-methyl isoflavone (DS45), stigmasterol (DS37), syringin (DS38), and HMF (DS75) with a CS sum of 45.20%; these were active ingredients from both ATR and CR, especially apigenin and HMF, the shared ingredients. For instance, syringin exhibits anti-inflammatory activity and enhances the synthesis of acetylcholine in the hippocampus [ 69 , 108 ]. HMF can mitigate the impairment of cognition and memory function induced by A β , inhibit beta-secretase activity, and increase antioxidative enzyme activities [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rosin (34) and eugenol glucoside (43) were isolated from fruits and flowers of AH, respectively [12,21]. Ferulic acid (35), syringin (37), and trans-coniferin (38) have been obtained from the roots of AH [19]. Meanwhile, trans-p-hydroxycinnamic acid (39), (E)-caffeic acid methyl ester (40), trans-coniferyl aldehyde (41), and trans-sinapaldehyde (42) were retrieved from the stem part of this plant [20].…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…Meanwhile, trans-p-hydroxycinnamic acid (39), (E)-caffeic acid methyl ester (40), trans-coniferyl aldehyde (41), and trans-sinapaldehyde (42) were retrieved from the stem part of this plant [20]. Additionally, caffeic acid (36) was purified from both roots and stems of AH [19,20] (Figure 6).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
See 1 more Smart Citation